Literary criticism and interactive advertising: Bakhtinian perspective on interactivity - Karimova, Gulnara Z. (My University, 2011)
This article examines interactivity using the concept of dialogic relationships introduced by Russian philosopher Mikhail Bakhtin and the concept of transtextuality, proposed by French literary theorist Gérard Genette. These concepts help to reveal two parallel strata of interactivity: the stratum of interactivity between the viewer and the message and the stratum of interactivity that exists inside the message and its surrounding. It concludes that interactivity can be conceived as a relation and that the message is a co-creation. The study contributes to the theory of interactivity, which challenges the existing and rather limited advertising theories and offers an alternative Bakhtinian perspective on the phenomenon of interactivity. © 2011 Walter de Gruyter.
Keywords: advertising; Bakhtin; dialogic relationships; Genette; interactivity; literary criticism; transtextuality